2018
DOI: 10.1186/s10020-018-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Stachydrine protects eNOS uncoupling and ameliorates endothelial dysfunction induced by homocysteine

Abstract: BackgroundHyperhomocysteinemia (HHcy) is an independent risk factor for cardiovascular diseases (CVDs). Stachydrine (STA) is an active component in Chinese motherwort Leonurus heterophyllus sweet, which has been widely used for gynecological and cardiovascular disorders. This study is aimed to examine the effects of STA on homocysteine (Hcy)-induced endothelial dysfunction.MethodsThe effects of STA on vascular relaxation in rat thoracic aortas (TA), mesenteric arteries (MA) and renal arteries (RA) were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
0
29
1
Order By: Relevance
“…Release of NO was also indirectly assessed by measuring the concentration of nitrite (NO 2 – ), a stable oxidization product of NO, in the supernatants of HUVECs. Using a Griess Reagent System kit according to the manufacturer's instructions, the nitrite concentration was determined spectrophotometrically at 550 nm [ 20 ]. The results were expressed as μM nitrite/10 5 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Release of NO was also indirectly assessed by measuring the concentration of nitrite (NO 2 – ), a stable oxidization product of NO, in the supernatants of HUVECs. Using a Griess Reagent System kit according to the manufacturer's instructions, the nitrite concentration was determined spectrophotometrically at 550 nm [ 20 ]. The results were expressed as μM nitrite/10 5 cells.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been found to improve cerebral ischemia-reperfusion injury in rats (Loh et al, 2010). Stachydrine, a major constituent of motherwort, can exhibit protective effects on vascular endothelial cells (ECs), as indicated by a recent study which reported that stachydrine reversed the Hcy-induced endothelial dysfunction and prevented eNOS uncoupling by increasing the expression of GTPCH1 and dihydrofolate reductase (DHFR) (Servillo et al, 2013;Xie et al, 2018). The low doses of stachydrine could inhibit hydrogen peroxide and induce myometrial smooth muscle cell apoptosis by upregulating Bcl-2 expression (Liu Xin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…After being washed, the blots were visualized by using the enhanced chemiluminescence (ECL) system. The eNOS dimerizations were assayed by using low‐temperature SDS‐PAGE as described previously (Xie et al, ). Briefly, protein lysates were mixed with loading buffer (without β‐mercaptoethanol) and without boiling before loading.…”
Section: Methodsmentioning
confidence: 99%